Communication Styles for Enhancing Patient Motivation in Spinal Tuberculosis Care - Sri Handayani; Leila Mona Ganiem (Athena: Journal of Social, Culture and Society, 2025)
This study examines the role of therapeutic communication styles in managing spinal tuberculosis (TB) care, emphasizing their impact on building trust, reducing anxiety, and motivating patient engagement. Employing a qualitative approach grounded in the post-positivist paradigm, the research was conducted at RS Premiere Bintaro with an orthopaedic surgeon and a purposive sample of spinal TB patients and their caregivers as participants. Data were collected through in-depth interviews and non-participatory observations, analyzed using a thematic framework. The findings reveal that communication styles such as Impression, Attentive, Open, and Friendly styles significantly enhance therapeutic relationships. The Impression Style fosters trust through positive first impressions, while the Attentive Style reinforces empathy and active listening, addressing psychological and emotional concerns. The Open Style empowers patients by providing transparent and comprehensive explanations, and the Friendly Style alleviates anxiety using humor and informal conversations. Additionally, involving caregivers using the Relinquishing Style underscores the importance of shared decision-making and collaborative care. This study highlights the necessity of adopting adaptable communication styles tailored to patient and caregiver needs in managing chronic conditions like spinal TB. It recommends integrating these styles into healthcare training programs, emphasizing the ethical use of humour and non-verbal communication to enhance patient comfort and adherence. Future research should explore diverse settings and larger sample sizes to validate these findings and extend their generalizability.